Une concertation restreinte pour définir l’intérêt général des espaces forestiers. Regard sur un paradoxe - Jacqueline Candau; Philippe Deuffic (VertigO)
Participation is frequently implemented to define localized common goods. The aim is to obtain a larger and more coherent legitimacy of the decisions compared to the traditional public action which supposes a preliminary conception of the general interest. In order to avoid the privatization of common goods by private interests, public policies tools recommend to associate a great diversity of actors with the deliberative process. Drawing on experience from a research program on multifonctionality of the forest in the south of France, we will wonder whether the implementation of these principles guarantees a more democratic definition of the public interest. It was observed that the discussions in connection with forest multifunctionality were mainly managed by forest actors. For as much, the problems resulting from the deliberative process do not confine the forest in a role of production. It assigns a fragile function of protection and especially a social function to it (recreational activities). We attend a publicisation of the forest whereas the frame of the participation forums cannot be described as democratic. This paradox questions us on the link commonly established between the stakeholders’ diversity and the protection of their private interests. We propose assumptions to explain this result which can appear paradoxical.